ANALISIS TINGKAT KEPUASAN PASIEN RAWAT JALAN TERHADAP KUALITAS PELAYANAN DI RSUD SEJIRAN SETASON KABUPATEN BANGKA BARAT - Bella Hardianti; Burhanuddin Bani; Andy Evans Gunadi (LPPM STIE PERTIBA Pangkalpinang, 2019)
Outpatient services are a form of general services or medical services to patients for the purpose of observation, diagnosis, treatment, rehabilitation, and other health services without requiring the patient to be hospitalized. Data for 2017 outpatient visits by Sejiran Setason Regional Hospital is 31, 307 patients. For 2018 outpatient visits increased by 33, 568 patients and for 2019 outpatient visits by 32, 157 patients. The purpose of this study was to determine the level of outpatient satisfaction with the quality of service at the Sejiran Setason Regional Hospital of West Bangka Regency in 2019. This research is a descriptive-analytic study with a survey approach using Cartesian diagrams and data retrieval using interview techniques through questionnaire sheets. The population of this study was all outpatients who visited the Sejiran Setason Regional Hospital in 2019 totaling 32, 157 people with a total sample of 150 people taken by quota sampling technique. The results found that the reliability dimension states the highest conformity level is 63. 35%. On the responsiveness dimension, the highest level of conformity is 77. 36%. At the highest tangible dimensions, the highest suitability was 62. 89%. In the assurance dimension, the highest conformity level is 59. 57%. On the empathy dimension, the highest conformity level is 67. 49%. The recommendation from this study is expected that the Sejiran Setason Regional Hospital pays attention to the delay in the schedule of doctor services. In responding to patient complaints doctors and nurses are expected to always be friendly and always make the effective communication. Increase the comfort of the treatment room by adding air conditioning. It is expected that checks are always carried out according to inspection standards. The hospital should pay attention to all complaints of patients and their families